Foodborne Parasites Dominate Current Parasitic Infections in Hunan Province, China - Liu, Xiaohua; Wu, Mengqi; Liu, Yuan; Li, Jing; Yang, Dongqian; Jiang, Liping (Frontiers in Cellular and Infection Microbiology, 2021)
Great progress has been made in the prevention and treatment of human parasitic diseases in China over the past six decades, but parasitic diseases are still one of the most serious public health problems in the world. The specific prevalence of parasitic diseases varies in different provinces due to their geographical environment and the dietary habits of people. In this study, a total of 4,428 patients suspected to have parasitic infection by clinicians or themselves from January 1, 2016, to December 31, 2020 were recommended to our laboratory for further testing. In total, 5,246 samples including fecal, blood, and other body fluids were detected by etiological and immunological methods. Approximately 15.20% (673/4,428) of all suspected patients were infected by at least one species of parasite, and the overall positive rate of suspected patients from Hunan Province was 15.10% (594/3,933). A total of 18 species of parasites, namely, nematodes (4 species), trematodes (5 species), cestodes (4 species), protozoa (2 species), and medical arthropods (3 species), and 3 of them were imported parasites outside of Hunan Province. There are 9 species of foodborne parasites, accounting for 89.92% (464/516) of patients infected by one species of parasite. Common parasites in Hunan Province include plerocercoid, Paragonimus westermani, Clonorchis sinensis, cysticercus, Toxoplasma gondii, and Schistosoma japonicum. In this study, we found that the incidence of soilborne nematode infections has decreased significantly. However, foodborne parasites gradually become the main parasitic infections as well as multiple infections are becoming more common. Therefore, we should not only continue the prevention and control of soil-derived nematodes but also focus on the prevention and control of foodborne parasites in the future.